Hubungan Pengetahuan, Sikap dan Kepatuhan Minum Tablet Fe Ppda Program Jufe (Jum’at Fe) dengan Kadar Hb (Hemoglobin) Remaja Putri di Sekolah Binaan Puskesmas Gekbrong Kabupaten Cianjur Tahun 2024 - Cincin Nuryanti; Retno Sugesti; Agus Santi br.Ginting (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Introduction: Haemoglobin levels are low (< 12 gr/dl) in adolescent women cause less blood (Anemia) causes to reduced focussing their study. JuFe programme is an innovation programme held by public health office of Cianjur through giving Fe tablets to adolescent women in Cianjur with consume Fe tablets every friday simultaneously in high schools. Objective: To determine the relationship between knowledge, attitude and compliance in JuFe programme with haemoglobin levels in adolescent women in the school partnership of Puskesmas Gekbrong Cianjur 2024. Method: This research used cross sectional study research design. The sampling technique is non random sampling are 35 peoples. The research instrument used a questionnaire, Results: This study found a relationship between knowledge (p=0,000), attitude (p=0,000), and compliance (p=0,000) with haemoglobin levels. Conclusion: there are the relationship between knowledge, attitude, and compliance in JuFe programme with haemoglobin levels in adolescent women in the school partnership of Puskesmas Gekbrong Cianjur 2024. Suggestion: It is the best health workers and teachers to increase education to adolescent women about low haemoglobin (Anemia) and implementing JuFe Programme routinely.